2009
DOI: 10.3168/jds.2009-2273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of detachment procedure and diet on recovery of solid-associated bacteria from sheep ruminal digesta and representativeness of bacterial isolates as assessed by automated ribosomal intergenic spacer analysis-polymerase chain reaction

Abstract: Six ruminally and duodenally cannulated sheep were used in a partially replicated 4 x 4 Latin square experiment designed to evaluate the efficiency of 3 detachment procedures (DP) to recover solid-associated bacteria (SAB) from ruminal digesta. The 4 experimental diets contained forage to concentrate (F:C) ratios of 70:30 or 30:70 with either alfalfa hay or grass hay as the forage. Bacterial biomass was labeled with 15NH4Cl. The DP were 1) MET: digesta was incubated at 38 degrees C for 15 min with saline solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…In the work by Allwood et al [23], bacteria were effectively removed from the cell culture samples by sequential washing in 0.2 % NaCl. Although there would be merit in separation of plant and attached bacteria in future studies, separation of colonising rumen bacteria from the forage substrate is difficult, usually requiring some form of chemical and physical treatment to enable detachment of a representative bacterial pool [4143]. In the current study it was considered that such processing could substantially alter the plant metabolome and so provide an erroneous impression of the interactome under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the work by Allwood et al [23], bacteria were effectively removed from the cell culture samples by sequential washing in 0.2 % NaCl. Although there would be merit in separation of plant and attached bacteria in future studies, separation of colonising rumen bacteria from the forage substrate is difficult, usually requiring some form of chemical and physical treatment to enable detachment of a representative bacterial pool [4143]. In the current study it was considered that such processing could substantially alter the plant metabolome and so provide an erroneous impression of the interactome under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A great proportion of the ruminal microorganisms can be attached to feed particles, especially in animals fed high-forage diets (Cheng et al, 1995;Yáñez-Ruiz et al, 2016). Previous studies (Martínez et al, 2009;Ramos et al, 2009a) showed that treating the ruminal contents with a Stomacher ® detached a greater percentage of solid-associated bacteria compared with other treatments, and produced ruminal fluid with the greatest similarity index between the bacterial communities in the rumen contents and in the resulting fluid. Our hypothesis was that including solid-associated bacteria in the inoculum (STO treatment) would result in improved fermentation, especially for high-fiber substrates.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis we used substrates of variable composition, and determined the main fermentation parameters at two incubation times (8 and 24 h), as differences between substrates may decrease or even disappear with increasing incubation time (Kamel et al, 2008;Mateos et al, 2014). Previous studies have investigated the effects of the processing method of rumen contents on gas production profiles (Cone et al, 1996;Lee et al, 2004;Pell and Schofield, 1993) and fermentation parameters (Lee et al, 2004;Rymer et al, 1999;Senshu et al, 1980), but few have looked into the effects on rumen microbial composition (Mackie et al, 1983;Martínez et al, 2009;Ramos et al, 2009a), and to our knowledge none has addressed both of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control method (MC) used to evaluate the efficiency of our new method was based on the conventional TRIzol-based RNA isolation technique that has been successfully used to extract RNA from various biological samples [22,23]. As undigested feed particle have been shown to prevent the TRIzol reagent from rapid sample penetration and to introduce a bias in the RNA recovered from microbial populations, samples are manually disrupted in liquid nitrogen using a mortar and pestle prior to exposing the samples to the TRIzol reagent, which enhances unbiased RNA recovery [21,24]. Using this control method we consistently obtained RNA yields >300 µg (352 µg and 538 µg total RNA from 1 gram rumen incubated corn stover and switchgrass, respectively), which is approximately four times more RNA than the 85 μg RNA from 1 gram of solid rumen content that was reported in a recent study in which the authors utilized a slightly altered version of this standard procedure [21].…”
Section: Discussionmentioning
confidence: 99%